Early rhythm control vs. rate control in atrial fibrillation: A systematic review and meta-analysis - Han, Shaojie; Jia, Ruikun; Cen, Zhifu; Guo, Ran; Zhao, Shenyu; Bai, Yixuan; Xie, Min; Cui, Kaijun (Frontiers in Cardiovascular Medicine, 2023)
Abstract Objective It has been argued for a long time whether rhythm control versus rate control strategies has differing effects on mortality and morbidity for atrial fibrillation (AF). Recently, several randomized controlled studies (RCTs) and observational trials described that an early rhythm management method was linked to a lower likelihood of negative clinical outcomes in individuals with AF. We wanted to see if an early rhythm management method may help patients with AF. Methods We performed a systematic search to retrieve studies assessing the outcomes of early rhythm control versus rate control in AF by using PubMed, Web of Science, Cochrane Library, and Embase published between 01/01/2000 and 15/04/2022. Results Finally, two RCTs, one retrospective analysis of RCT, and four observational studies were identified. Compared with rate control, early rhythm control has been linked to lower all-cause mortality. (risk ratio [RR], 0.76; 95% CI 0.69–0.83; P< .00001; I2 =77%). The use of early rhythm control was also linked to a lower risk of cardiovascular mortality (RR, 0.70; 95% CI 0.68-0.72; P < .00001; I2 =33), stroke (RR, 0.77; 95% CI 0.67-0.87; P < .001; I2 =64) and heart failure hospitalization (RR, 0.74; 95% CI 0.59–0.93; P=.0009; I2=93%) and we found no significant difference in nights spent in hospital per year, acute coronary syndrome or major bleeding between the groups. Conclusions In this meta-analysis including early rhythm control of individuals with AF, early rhythm therapy was linked to a lower risk of all-cause mortality, cardiovascular mortality, stroke, and heart failure hospitalization compared with rate therapy.